Aplikasi Penjadwalan Produksi Dan Pemesanan Sandal Pada Cv Toyobo Berbasis Android Dengan Metode Earliest Due Date - Nia Saurina; Lestari Retnawati; Firman Hadi Sukma Pratama (Jurnal Sistem Informasi dan E-Bisnis, 2024)
CV. TOYOBO is a company which engage in manufacturing of slippers, who produce slippers for children and adults. This company is allocated in Sidoarjo, East Java, have problem in receipt of order from customer, scheduling order until monitoring delivery those order. All decision which taken for those company are taken from leader CV. TOYOBO and mostly based on leader’s experience, there is no planning and scheduling for production. Customer from CV. TOYOBO divide in two categories there are domestic customer and abroad customer. If there is delay from supply order for domestic customer, then company are loss of profit 0.8% from total profit should be obtained and loss customer satisfaction, remember there are many companies that have same business. Whereas if there is delay from supply order for abroad customer, then company are loss of profit 1% from total profit should be obtained from customer.Result from research testing that this application could booking slipper and customer could make payment via email. Also this application could make production scheduling use Earliest Due Date (EDD) method.